YUK LES: INFORMATION SYSTEMS ON ONLINE PRIVATE COURSE SERVICES BASED ON MOBILE APPLICATION - Lydia Liliana; Adam Surya Wijaya; Nico Fernando; Henny Hartono; Dwi Hosanna Bangkalang (JBASE - Journal of Business and Audit Information Systems, 2019)
One way to improve students' academic and non-academic abilities is by taking tutoring. Tutoring is an effort to achieve maximum learning outcomes in accordance with the field of interest. In the era of technological revolution 4.0, we are always demanded to be up to date on their abilities in non-academic / soft skills such as video editing, programming, dance, music, multimedia, etc. Education 4.0 should be able to provide easy access to education and mobility in learning formal and non-formal fields. The application "Yuk Les" brings together the community / students who need private tutoring and people who have abilities in various non-academic fields based on Android. With this application, it is expected to facilitate the public in finding private lessons in accordance with the needs of the field of interest and opening new jobs for the community / students who have abilities in non-academic fields.